Knowledge, attitude and practice towards available anti-smoking campaign among adults in Kuantan - Jaafar, Mohamad Helmy; Alias, Normalina; Mat Yusof, Afzan; Md Isa, Muhammad Lokman (UPM Press, 2019)
Introduction: This study was conducted to determine the association between knowledge, attitude and practice among Kuantan community towards anti-smoking campaign. An anti-smoking campaign can be referred to as a series of ads programs that are introduced through various objective approaches to give awareness to people on the negative impacts of smoking behavior. The objectives of this study are (i) to investigate the association between socio-demographic data (gender, income, education level) and level of knowledge towards anti-smoking campaign; (ii) to find out the association between socio-demographic data (gender, income, education level) and level of attitude against anti-smoking campaigns; (iii) to study the association between socio-demographic data (gender, income, education level) and level of practice towards anti-smoking campaigns; and (iv) to find out the correlation between level of knowledge with level of attitude, level of knowledge with level of practice, and level of attitude with level of practice towards anti-smoking campaigns. Methods: A descriptive cross-sectional study was conducted among adult Kuantan community and convenience sampling was used to collect the data. A validated questionnaire was used to collect data. Statistical analysis of the data was carried out using SPSS and association of variables was analysed using Chi-square test. Results: This study found that level of knowledge did not affect the attitude level of the community. However, level of knowledge did affect the level of practice towards the anti-smoking campaign. Conclusion: It revealed that respondents with high level of knowledge also had good level of practice towards anti-smoking campaign.